Hollywood independents : the postwar talent takeover - Mann, Denise (Commerce and mass culture series., 2008)
Hollywood Independents explores the crucial period from 1948 to 1962 when independent film producers first became key components of the modern corporate entertainment industry. Denise Mann examines the impact of the radically changed filmmaking climatethe decline of the studios, the rise of television, and the rise of potent talent agencies like MCAon a group of prominent talent-turned-producers, including Burt Lancaster, Joseph Mankiewicz, Elia Kazan, and Billy Wilder. In order to show how these newly independent filmmakers negotiated through an increasingly fraught, reactionary creative at.